# Difference quotient for $$$f{\left(x \right)} = x^{2} + 6 x - 7$$$

### Your Input

**Find the difference quotient for $$$f{\left(x \right)} = x^{2} + 6 x - 7$$$.**

### Solution

The difference quotient is given by $$$\frac{f{\left(x + h \right)} - f{\left(x \right)}}{h}$$$.

To find $$$f{\left(x + h \right)}$$$, plug $$$x + h$$$ instead of $$$x$$$: $$$f{\left(x + h \right)} = \left(x + h\right)^{2} + 6 \left(x + h\right) - 7$$$.

Finally, $$$\frac{f{\left(x + h \right)} - f{\left(x \right)}}{h} = \frac{\left(\left(x + h\right)^{2} + 6 \left(x + h\right) - 7\right) - \left(x^{2} + 6 x - 7\right)}{h} = h + 2 x + 6$$$.

### Answer

**The difference quotient for $$$f{\left(x \right)} = x^{2} + 6 x - 7$$$A is $$$h + 2 x + 6$$$A.**